Donepezil's Effects on Brain Functions of Patients With Alzheimer Disease: A Regional Homogeneity Study Based on Resting-State Functional Magnetic Resonance Imaging. Issue 2 (March 2019) - Cheng, Jianan; Yang, Hua; Zhang, Jiangtao
Abstract : Purpose: Donepezil is known to increase cholinergic synaptic transmission in Alzheimer disease (AD), although how it affects cortical brain activity and how it consequently affects brain functions need further clarification. To investigate the therapeutic mechanism of donepezil underlying its effect on brain function, regional homogeneity (ReHo) technology was used in this study. Patients and methods: This study included 11 mild-to-moderate AD patients who completed 24 weeks of donepezil treatment and 11 matched healthy controls. All participants finished neuropsychological assessment and resting-state functional magnetic resonance imaging scanning to compare whole-brain ReHo before and after donepezil treatment. Results: Significantly decreased Alzheimer's Disease Assessment Scale–Cognitive Subscale scores ( P = 0.010) and increased Mini-Mental State Examination scores ( P = 0.043) were observed in the AD patients. In addition, in the right gyrus rectus ( P = 0.021), right precentral gyrus ( P = 0.026), and left superior temporal gyrus ( P = 0.043) of the AD patients, decreased ReHo was exhibited. Conclusion: Donepezil-mediated improvement of cognitive function in AD patients is linked to spontaneous brain activities of the right gyrus rectus, right precentral gyrus, and left superior temporal gyrus, which could be used as potential biomarkers for monitoring the therapeutic effect of donepezil.